Assessment of 8-hydroxy-2-deoxyguanosine activity, apoptosis, acetylcholinesterase and antioxidant enzyme activity in Capoeta umbla brain exposed to chlorpyrifos - Kirici Mahinur (Oceanological and Hydrobiological Studies)
In this study, neurotoxic responses to exposure to chlorpyrifos (CPF) at different doses (55 and 110 μg l-1) and at different time intervals (24 and 96 h) were investigated in Siraz fish (Capoeta umbla) using 8-hydroxy 2-deoxyguanosine (8-OHdG) activity, caspase-3, acetylcholinesterase (AChE) and oxidative stress parameters [malondialdehyde (MDA), catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx) and glutathione reductase (GR)]. In this study, the LC50 value of CPF was determined for the first time for C. umbla and calculated as 440 μg l-1. In this study, 12.5% (55 μg l-1) and 25% (110 μg l-1) of the LC50 value were used. The obtained data indicate a significant increase in the MDA level and inhibition of antioxidant enzymes in the brain (p < 0.05). Considering DNA damage and the apoptotic process, no significant changes were found in 8-OHdG and caspase-3 activity at both doses exposed for 24 h, but a significant increase was detected in both markers at 96 hours compared to the control group (p < 0.05). In the case of AChE activity, which is one of the neurotoxic markers in the brain, while inhibition was determined only at the high concentration (110 μg l-1) at the end of 24 hours, a decrease in enzyme activity was observed at the end of 96 hours in both concentration groups. In the light of all these results, we can say that CPF showed inhibitory effects on enzyme activity and inducing effects on MDA, caspase-3 and 8-OHdG levels. Based on these results, it can be concluded that CPF contributes to oxidative stress in fish and may have neurotoxic effects.